2021
DOI: 10.1055/a-1577-9755
|View full text |Cite
|
Sign up to set email alerts
|

The Renaissance of Alkali Metabisulfites as SO2 Surrogates

Abstract: The upsurge of interest in the development of methodologies for the construction of sulfur-containing compounds via the use of expedient reagents has been established as sustainable tools in organic chemistry. This review focuses on the sulfonylation reactions using inorganic sulfites (Na2S2O5 or K2S2O5) as the sulfur dioxide surrogate. Unlike bis-adduct of DABCO, which is an excellent surrogate of the gaseous SO2, the use of sodium or potassium metabisulfites as SO2 surrogates are equally efficient. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 81 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…Sulfinate salts are versatile intermediates used in the synthesis of a variety of sulfonyl-derived functional groups that are frequently found in agrochemicals and pharmaceuticals . Bench-stable SO 2 surrogates, such as the amine–SO 2 Lewis adduct DABSO (DABCO·(SO 2 ) 2 ), or inorganic metal bisulfites, such as Na 2 S 2 O 5 , used in combination with metal catalysts, organometallic reagents, , or reactive intermediates, have made a tremendous impact on the synthesis of aryl sulfinates. However, applications to the preparation of alkyl sulfinates are more limited.…”
mentioning
confidence: 99%
“…Sulfinate salts are versatile intermediates used in the synthesis of a variety of sulfonyl-derived functional groups that are frequently found in agrochemicals and pharmaceuticals . Bench-stable SO 2 surrogates, such as the amine–SO 2 Lewis adduct DABSO (DABCO·(SO 2 ) 2 ), or inorganic metal bisulfites, such as Na 2 S 2 O 5 , used in combination with metal catalysts, organometallic reagents, , or reactive intermediates, have made a tremendous impact on the synthesis of aryl sulfinates. However, applications to the preparation of alkyl sulfinates are more limited.…”
mentioning
confidence: 99%
“…Patel's review has summarized recent advancements in sulfonylation reactions using K 2 S 2 O 5 or Na 2 S 2 O 5 as the SO 2 source [6b] . To avoid duplication, we only select some reactions to illustrate the characteristics of sulfite salts in MCRs.…”
Section: Multicomponent Sulfonylation Involving Inorganic Sulfite Saltsmentioning
confidence: 99%
“…Despite a few reported examples of sulfonated azaspiro­[4,5]-trienones and azaspiro­[4,5]-decanes in recent years, they are limited to sulfone preparation and are typically unable to undergo further modification. In 2021, Wang’s group published the pioneering study on the sulfonation of electron-deficient alkenes using SO 3 – radicals for the synthesis of oxindole-based sulfonates . Recently, we have shown that the combination of Mn­(OAc) 3 and K 2 S 2 O 5 can effectively promote the oxidative sulfonation of functionalized alkenes via SO 3 – radicals as the key intermediate (Scheme A) . This success was attributed to the development of a suitable oxidative environment that matched well with the reactive SO 3 – radical.…”
Section: Introductionmentioning
confidence: 99%